Soret and Dufour effects on doubly diffusive convection of nanofluid over a wedge in the presence of thermal radiation and suction - Kasmani, Ruhaila Md.; Sivasankaran, S.; Bhuvaneswari, Marimuthu; Alshomrani, A.S.; Siri, Zailan (Sharif University of Technology, 2019)
This paper investigates the effects of thermal radiation, Dufour, and Soret effects on doubly diffusive convective heat transfer of nanoliquid over a wedge in the presence of wall suction. The governing equations are transformed to nonlinear ordinary differential equations using similarity transformation. The resulting system is solved numerically by the fourth-order Runge-Kutta-Gill method with a shooting technique and a Newton-Raphson method. The solutions are expressed in terms of velocity, temperature, solutal concentration, and volume fraction profiles. The effects of pertinent parameters involved in the problem such as wedge angle, thermal radiation, Brownian motion, thermophoresis, Soret number, and Dufour number on the skin friction coefficient, local Nusselt number, and local Sherwood number are discussed in detail. © 2019 Sharif University of Technology. All rights reserved.